Mesenchymal stem/stromal cell therapy for COVID-19 pneumonia: potential mechanisms, current clinical evidence, and future perspectives - Yao, Weiqi; Shi, Lei; Zhang, Yun; Dong, Haibo; Zhang, Yu (Stem cell research & therapy, 2022)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread into more than 200 countries and infected approximately 203 million people globally. COVID-19 is associated with high mortality and morbidity in some patients, and this disease still does not have effective treatments with reproducibly appreciable outcomes. One of the leading complications associated with COVID-19 is acute respiratory distress syndrome (ARDS); this is an anti-viral host inflammatory response, and it is usually caused by a cytokine storm syndrome which may lead to multi-organ failure and death. Currently, COVID-19 patients are treated with approaches that mostly fall into two major categories: immunomodulators, which promote the body’s fight against viruses efficiently, and antivirals, which slow or stop viruses from multiplying. These treatments include a variety of novel therapies that are currently being tested in clinical trials, including serum, IL-6 antibody, and remdesivir; however, the outcomes of these therapies are not consistently appreciable and remain a subject of debate. Mesenchymal stem/stromal cells (MSCs), the multipotent stem cells that have previously been used to treat viral infections and various respiratory diseases such as ARDS exhibit immunomodulatory properties and can ameliorate tissue damage. Given that SARS-CoV-2 targets the immune system and causes tissue damage, it is presumable that MSCs are being explored to treat COVID-19 patients. This review summarizes the potential mechanisms of action of MSC therapy, progress of MSC, and its related products in clinical trials for COVID-19 therapy based on the outcomes of these clinical studies.